Surface modification of h‐BN and preparation of h‐BN/PEI thermally conductive flexible films. Issue 6 (14th April 2022) - Luo, Wenhao; Zeng, Jinling; Chen, Yanrong; Dai, Wenbin; Yao, Yingbang; Luo, Bing; Zhang, Fuzeng; Wang, Tingting
Abstract: Hexagonal boron nitride (h‐BN) micro‐platelets were surface‐functionalized by sulfuric acid (SA). Such modified h‐BN powders were mixed with thermoplastic polyether imide (PEI) to prepare flexible composite films using a solution casting method. After surface modification, the h‐BN powders were uniformly dispersed in the PEI matrix. The thermal conductivity of the flexible composite materials was significantly improved, with a 60% increase over that of pure PEI. The mechanical properties of the composites were also measured and discussed. The Young's modulus of the h‐BN/PEI composites was increased from 1.15 GPa for pure PEI to 1.62 GPa for the h‐BN/PEI composite with a filling ratio 10 vol%. As compared to pure PEI film, the electrical breakdown strength of the composites with 5 vol% h‐BN increased from 45.3 to 55.3 kV/mm. Our results show that the surface‐modified h‐BN filler is effective in improving the thermal conductivity and insulation performance of PEI‐based composites. Abstract :